Effects of autogenic and imagery training on the shooting performance in biathlon - Groslambert, A.; Candau, R.; Grappe, F.; Dugue, B.; Rouillon, J. D. (Research Quarterly for Exercise and Sport, 2003)
It is discussed how a special training programme with autogenic and imagery training (AT+IM) can influence the shooting performance in biathlon. The experiment was carried out with 16 biathletes from the French national team (4 women, 12 men). The results show that this training program with AT+IM offers value improvements in the standing shooting by increasing biathletes' postural control and hold stability. This improvement in shooting would result in a time gain estimated at 35 s in a 10-km-race and 70 2 in a 20-km-race.